Global System for Mobile Communication Based Automated Billing System for Electric Energy Meter - Chai , Ri Feng; Chua King Lee (Evolution in Electrical and Electronic Engineering, 2021)
The bill of electricity usage typically is manually recorded. This practice is affected by human proficiency and during pandemic Covid-19, it causes the delivery of bill left behind the schedule. Thus, this paper presents the development of automatic electricity reading, recording and billing system using a microcontroller device. The system utilizes Arduino Uno, DS1307 real-time clock (RTC), liquid crystal display (LCD) and global system for mobile communication (GSM) to develop the prototype of the billing system. In this system, the mobile phone is an intermediate platform between a circuit for reading electricity and the Firebase online database which is acquired to store the reading of the circuitry. Thunkable software is used to develop a graphical user interface (GUI) application to access the cloud database, perform necessary calculations and show associated information to users. In conclusion, the prototype of the billing system is successfully being developed and it able to perform billing calculations, sends the billing cost via Short Message Service (SMS) and displays the billing cost on GUI.